The Influence of Brand and Venue Image on the Decision to Buy a Stand at the Chengbeng Food Fest Medan 2025 Event by CV Vinkoo Jakarta Fest - Harahap, Fiqri Akbar Habibie; Sari, Dewi Comala (CV. Civiliza Publishing, 2025)
In culinary events or bazaars, tenant stands play a crucial role in the success of the event. Therefore, companies must convince tenants to purchase stands by focusing on factors such as Brand Image and Venue. This study aims to examine the influence of Brand Image and Venue on the Stand Purchase Decision at the ChengBeng Food Fest Medan 2025 organized by CV Vinkoo Jakarta Fest. This quantitative research employed a saturated sampling technique with a total of 44 tenant stands. Data were collected through questionnaires. The results indicate that both Brand Image and Venue have a positive and significant influence, both partially and simultaneously, on the Stand Purchase Decision. The coefficient of determination (R²) of 87.7% suggests that these two variables account for most of the purchase decision, while the remaining 12.3% is influenced by other factors such as price, facilities, company image, and event organizer quality.